A new soil-dwelling palpigrade species from Northern Italy (Palpigradi: Eukoeneniidae) - Christian, Erhard (Zootaxa, 2009)
Among the 27 palpigrade species recorded in Europe so far, 23 occur in caves or narrow subterranean voids. Eukoenenia gallii n. sp. from a cork oak forest on the Italian Riviera (Liguria) is added to the small group of edaphic European palpigrades. E. gallii is not closely related to the common soil-dweller E. mirabilis (Grassi & Calandruccio, 1885), but to E. subangusta (Silvestri, 1903). Body shape and proportions make the new species look extremely edaphomorphic. All instars are described and illustrated with light micrographs of diagnostic traits.